SUPPLY CHAIN MANAGEMENT AND PERFORMANCE: EVIDENCE FROM MANUFACTURING ORGANISATIONS IN NIGERIA (Journal of Technology and Operations Management, 2022)
This study examined how supply chain management practices (SCM) impact on the performance of selected quoted manufacturing organizations in Nigeria. These practices include procurement outsourcing, information flow management and order process management. Survey research was used through questionnaire administration to the staff of production, procurement, warehouse, logistics and marketing departments of two quoted manufacturing organizations operating in Edo state. Statistical tools used in analyzing the data obtained include mean, standard deviation, correlation and regression analyses. The study found that positive and statistically significant relationship exists between supply chain management practices such as procurement outsourcing, information flow management and order process management, and performance of manufacturing organizations. The study, therefore, recommends that manufacturing organizations should concentrate on the production and services they have the expertise on and outsource those functions other firms or individual can do better for them.